ABO and Rh blood groups frequency in men, women and neonates in Diyarbakir province (Annals of Medical Research, 2021)
Aim: In this study, our objective was to determine the distribution of the blood groups among females, males, and neonates along with the overall analysis of Rh and ABO blood group systems in Diyarbakır region and contribute particularly to the blood group database for neonates, as there is no other study focused on the blood groups in neonates in particular. Material and Methods: The data of 127,091 patients, who had applied for the determination of their blood groups or were hospitalized and needed the determination of their blood groups between January 2016 and July 2019, were analyzed in this retrospective study. Results: In our study, the distribution of subgroups of the ABO system without considering the Rh system was as follows: 39.69% A, 33.62% O, 18.63% B, and 8.06% AB. The same rates were 36.79% A, 34.6% O, 20.77% B, and 7.84% AB among neonates. The comparison of the general population (females and males) with the neonates showed that group A was 3 percent lower and group B was 2 percent higher among neonates. We believe our study is important, as it is the only single-center study focused on three groups (females, males, and neonates) and conducted in the Research and Training Hospital in Diyarbakır.Conclusion: We believe that the differentiation in the distribution of ABO blood subgroups among neonates will also contribute to the literature as an important finding, which may depend on the social events like the increased number of Syrian refugees and domestic migrations.
Keywords: ABO and Rh (D) blood groups; Diyarbakir; Frequency; Neonates